USULAN PREVENTIVE MAINTENANCE DENGAN METODE RELIABILITY CENTERED MAINTENANCE UNTUK MEMINIMALKAN BIAYA PERAWATAN MESIN - Afif Hakim; Annisa Indah Pratiwi; Anggi Prasetyo (Industry Xplore, 2020)
The number of frequencies of damage to aluminum machines at PT. XYZ in one year by 39 times. This frequency is large enough that it is necessary to carry out effective maintenance activities to reduce the amount of damage. Reliability Centered Maintenance is one of the methods used to determine how to maintain machine components that fail according to the criticality level of a component. The results of the analysis of the Reliability Centered Maintenance method at the FMEA stage found 1 component that has a high critical level with the highest RPN value of 144, namely the loader component. The selection of actions to be carried out by conditional directed or scheduled on-condition tasks is because these components will function properly if component replacement or repair is carried out. The minimum maintenance cost for loader components obtained from the calculation is Rp. 11,961,496,-